Environmental Impact of Coronavirus disease (COVID-19) Pandemic around the World with a Special Focus on Thailand and India: A rapid review - Aroonsrimorakot, Sayam; Laiphrakpam, Meena (Naresuan University Journal: Science and Technology (NUJST); Vol 31 No 2 (2023): April-June 2023DO - 10.14456/nujst.2023.16, 2023)
COVID-19, scientifically called Novel Coronavirus SARS – CoV-2 which was first identified in Wuhan, Hubei Province, China, has infected above 118,000 persons in more than 114 countries worldwide on 11 March 2020, and so the World Health Organization announced coronavirus disease (COVID-19) as a pandemic. The study aims to review the positive as well as negative environmental impact of the COVID-19 pandemic around the World, with a special focus on Thailand, and India.  The study reviews documents and collects relevant data, related to COVID-19 and the environment in the world, particularly Thailand and India, from the beginning of the outbreak in January 2020 till February 2021 from various kinds of electronic documents available on various publication sites, the daily internet media, social media, news, and opinions, during 2020-2021 by typing keywords as “Environmental impact of COVID-19”. It is found that coronavirus disease has impacted the World, Thailand, and India’s environment both positively and negatively through several indicators including improvement in air quality, clean beaches, reduction in surface temperature and environmental noise, freedom of movement to wildlife, birds, animals, regeneration of biodiversity, and water bodies. Even though the pandemic has caused many environmental benefits, it caused an alarming situation in the amount of generated disposable packaging, plastic, medical waste, and the management of its disposal. It can be concluded that human behavior and activities, indeed impacted the environment, so the solution to the environmental crisis depends on changing human behavior and activities that cause the deterioration of the environment. Keywords: COVID-19, Positive environmental impact, Negative environmental impact, SARS-CoV-2, Pandemic